Advanced Aquaponics Monitoring System Using Raspberry Pi3 - et. al., S. Rangeetha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper describes the concept of Aquaponics, including a brief history of its development and its place within the larger category of soil-less culture which is or else called Modern agriculture. Aquaponics system refers to the system that chains conventional aquaculture with hydroponics in a symbiotic environment. In normal Aquaculture, excretions from the animals being raised can accumulate in the water, increasing harmfulness. In an aquaponics system, water from an aquaculture system is nourished to hydroponic system where the by-products are broken down initially into nitrites and consequently into nitratesby nitrifying bacteria, which are consumed by the plants as nutrients, and the water is then recirculated back to the aquaculture system.The proposed Aquaponics system is based on food growth in Hydroponics and using Aquafarming techniques. The proposed system collects data acquired by the device and gives alert by sending message and activating the buzzer.